2017
DOI: 10.3390/su9111948
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Rural and Urban Development: Applying Coordinated Urban–Rural Development (CURD) Strategy to Achieve Sustainable Urbanisation in China

Abstract: Land in rural China has been under a separate and closed management system for decades even after the urban land reform that started in the late 1980s. The blurred property rights over rural land have been hindering the rural welfare as surplus rural land in sub-urban areas cannot be circulated into more economic use without first being requisitioned by the state. This traditional conversion process creates a lot of problems, among them are the compensation standard as well as displacement of rural residents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…For example, Zhao Xu et al [8] analyzed the impact of out-migration agricultural resettlement on land disposal behavior and livelihood transition of reservoir migrants in the middle route of the South-to-North Water Transfer Project, and then suggested a resettlement model with no or little land. Ling-Hin Li [9] found that a centralized resettlement model significantly reduced the probability of relocation households choosing a diversified livelihood compared with the scattered resettlement model. Tian Peng et al [10] conducted an in-depth analysis of a community in Xinxiang, Henan province based on the "urban and rural continuum" framework, concluding that new urbanized communities are characterized by integrated infrastructure and public services, diversified livelihood models, and the implementation of new community governance models.…”
Section: Sustainable Livelihood Issues Of Urban Resettlementmentioning
confidence: 99%
“…For example, Zhao Xu et al [8] analyzed the impact of out-migration agricultural resettlement on land disposal behavior and livelihood transition of reservoir migrants in the middle route of the South-to-North Water Transfer Project, and then suggested a resettlement model with no or little land. Ling-Hin Li [9] found that a centralized resettlement model significantly reduced the probability of relocation households choosing a diversified livelihood compared with the scattered resettlement model. Tian Peng et al [10] conducted an in-depth analysis of a community in Xinxiang, Henan province based on the "urban and rural continuum" framework, concluding that new urbanized communities are characterized by integrated infrastructure and public services, diversified livelihood models, and the implementation of new community governance models.…”
Section: Sustainable Livelihood Issues Of Urban Resettlementmentioning
confidence: 99%
“…Once the gap between urban and rural areas continues to widen, it will lose social equity and cause serious social problems. To realize better and faster development of the regional economy and society, urban–rural harmony development is inevitable (Li, ; Li, ; Long, , ; Tu & Long, ; Yang & Xu, ). Urban–rural harmony development refers to drawing up the economic and social development plans of urban and rural areas uniformly as one entity (Zhong, Li, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the educational backgrounds of participants and the overall quality of their contribution is uneven. In fact, the percentage of construction participants in China having a bachelor's degree or higher is very low [6,7]. Hence, the probability of the behavioral risk among principal construction participants in China is very high.…”
Section: Introductionmentioning
confidence: 99%